Regulation of Cell Cycle - Rachmat Hidayat; Hayati, Lusia (Biomedical Journal of Indonesia, 2020)
The cell cycle is a vital process in the life of every organism. Normally, the cell cycleresults in cell division. Cell division consists of 2 main processes, namely DNAreplication and chromosome division that has been duplicated into 2 daughter cells.Cyclin is expressed periodically so that the cyclin concentration varies at each phase ofthe cell cycle. Cdks are threonine or serine protein kinases which must bind to cyclinfor its activation. The concentration of Cdks is relatively constant during the cell cycle.Cyclin-dependent kinase inhibitor (CKI) is a protein that can inhibit Cdk activity bybinding to Cdk or the cyclin-Cdk complex